2021
DOI: 10.1111/gfs.12528
|View full text |Cite
|
Sign up to set email alerts
|

Root growth response of serradella species to aluminium in solution culture and soil

Abstract: Acid soils limit plant productivity globally with approximately 4.5% of arable land considered acidic (pH < 5.5) (von Uexküll & Mutert, 1995). Acid soils are common in the higher rainfall regions of southern Australia; extractable aluminium (Al) in these soils can reach concentrations that are toxic for root growth in many crop and forage species (Pinkerton & Simpson, 1982). Al toxicity reduces root elongation and proliferation (Foy, 1974), lateral root growth, and root hair length and density (Care, 1995; Hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…Malate is involved in the chelation of Al 3+ in acidic soils by occupying soil sorption sites commonly occupied by P, allowing more P to remain in the soil solution for plant uptake (Basu et al, 1994; Cocker et al, 1998). Malate efflux is a recognised Al 3+ tolerance mechanism in wheat (Delhaize, Ryan, & Randall, 1993): the significantly greater malate amount found in serradella and subterranean clover will chelate even greater concentrations of exchangeable Al which likely contributes to their tolerance of acidic soils and aluminium (Kidd et al, 2021). Despite this, large amounts of malate and citrate do not appear to contribute to P acquisition in these pasture legumes, as shoot tissue P concentrations in both the limed and unlimed treatment were <0.2% (data not shown), well below what is considered optimum (≥0.4%) for plant growth (Reuter & Robinson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Malate is involved in the chelation of Al 3+ in acidic soils by occupying soil sorption sites commonly occupied by P, allowing more P to remain in the soil solution for plant uptake (Basu et al, 1994; Cocker et al, 1998). Malate efflux is a recognised Al 3+ tolerance mechanism in wheat (Delhaize, Ryan, & Randall, 1993): the significantly greater malate amount found in serradella and subterranean clover will chelate even greater concentrations of exchangeable Al which likely contributes to their tolerance of acidic soils and aluminium (Kidd et al, 2021). Despite this, large amounts of malate and citrate do not appear to contribute to P acquisition in these pasture legumes, as shoot tissue P concentrations in both the limed and unlimed treatment were <0.2% (data not shown), well below what is considered optimum (≥0.4%) for plant growth (Reuter & Robinson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the need of the hour is to enhance the cultivation and yield of medicinal plants.  In the existing research works, either the root [24,[35][36][37] or the shoot growth responses are monitored [25,28,[38][39][40] not both.  The comparative growth responses of any plant are carried out only in any one medium, growth responses in multiple mediums are not analyzed for a single plant [24,28,[30][31][32][33][34][35][36].…”
Section: Figure 2 Major Utilities Of Onionmentioning
confidence: 99%
“…Very few works have focused on the better qualitative and quantitative yield of the root as well as the shoot of any medicinal plant [27-32, 35, 36]. Some of the research works focus on only the root [24,[35][36][37] or only the shoot of any plant [25,28,[38][39][40]. This work demonstrates the root and shoot growth responses of a medicinal plant (onion) having abundant medicinal properties in its shoot as well as its root.…”
Section: Figure 2 Major Utilities Of Onionmentioning
confidence: 99%
“…A range of cultivars of both species are now available in Australia, often with higher levels of hard seeds and high tolerance of soil aluminium concentrations (Loi et al . 2005; Kidd et al . 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sandral et al (2019) demonstrated that both French serradella (Ornithopus sativus Brot) and yellow serradella (Ornithopus compressus L.) could be used in a pasture system requiring less P fertiliser, without compromising forage yield, compared to subterranean clover. A range of cultivars of both species are now available in Australia, often with higher levels of hard seeds and high tolerance of soil aluminium concentrations (Loi et al 2005;Kidd et al 2021). However, these cultivars were primarily developed for drier environments in mixed cropping zones in Western Australia, the Riverina and in the North West Slopes and Plains regions of NSW (Freebairn 1990;Howieson et al 2000;Loi et al 2005).…”
Section: Introductionmentioning
confidence: 99%